Problem-Based Learning Supported with Experiment Media Based on the Internet of Things to Enhance the Students’ HOTS Ability - Yeni Rima Liana; Suharto Linuwih; Sulhadi Sulhadi (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
This study aims to analyze the feasibility and effectiveness of experiment media based on Internet of Things (IoT) to enhance the students' HOTS ability on thermodynamics law material. This Research and Development comprises of the following stages: (1) defining needs, (2) designing products, (3) developing products, and (4) disseminating products. Four expert lecturers and two physics teachers serve as the validator. The limited trial subjects consisted of six students of class XI MIPA SMAN 1 Pekalongan; the field test subjects consisted of 108 students who were randomly selected from all XI MIPA classes at SMAN 2 Batang, and the disseminating subjects were teachers of MGMP physics in Batang. The instruments used were expert validation questionnaires, teacher response questionnaires, student response questionnaires, and written tests. The results of the validation of media experts were 3.81 (very good), and material experts were 3.54 (very good). Meanwhile, the results of teacher responses were 3.92 (very good), and the results of student responses were 3.50 (very good). The effective contribution of the IoT-based experimental media to improve the ability of HOTS can be seen from the results of the Multivariate Test analysis on GLM based on the partial eta squared value of 85.9%. This shows that experiment media based on IoT is feasible and effective to enhance the students’ HOTS ability.